Three Novel COVID-19 Pneumonia Cases Successfully Treated With Lopinavir/Ritonavir - Wada, Tatsuhiko; Shimode, Kosuke; Hoshiyama, Takayuki; Takayama, Yoko; Yamaoka, Kunihiro (Frontiers in Medicine, 2020)
After the first case of Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus -2 (SARS-Cov-2) at Wohan, China in December 2019, it has spread world-widely. An outbreak in Japan occurred in a cruise ship followed by community-acquired COVID-19. Herein, we report 3 cases of COVID-19 that presented pneumonia following admission to Kitasato University Hospital. Patients were admitted based on the positive result of a real-time reverse transcriptase–polymerase chain reaction (RT-PCR) tests for COVID-19 nucleic acid. All patients were diagnosed as suffering from Non-severe COVID-19 pneumonia and successfully treated with Lopinavir / Ritonavir (LPV/r). LPV/r could be an option for treating Non-severe COVID-19 pneumonia in general and even in elderly patients.